Pengaruh Strategi Ketangguhan Mental Terhadap Motivasi Berprestasi Atlet - Novita Maulidya Jalal; Rizqi Amaliah; Rieska Cendra Ayu Wardhani; Rifqah Rifqah; Fadhel Muhammad; Muhammad Fadhil Ajra (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
The purpose of this study was to determine whether there was an effect of psychoeducation on mental toughness on the motivation of athletes' achievement during coaching. This psychoeducation is carried out in the form of non-training by conducting seminars by invited speakers from the team of facilitators and conducting discussion sessions with the coaches of the South Sulawesi Indonesian Esports Community (ESI Sul-Sel). This study uses a research design One-Group Pretest-Posttest Design, with 6 subjects with a percentage of 3 men (50%) and 3 women (50%). The data were analyzed using descriptive statistics, and based on the results of inferential statistical analysis with using the t test formula. The mean value obtained from the pre-test results was 2.66 and after the provision of psychoeducational material the post-test mean value was 5.33. Because tcount ttable is at a significance level of 0.05, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted, which means that there is an influence of psychoeducation on mental toughness on athletes' achievement motivation during coaching.Tujuan penelitian ini adalah untuk mengetahui apakah ada pengaruh psikoedukasi ketangguhan mental terhadap kotivasi berprestasi atlet selama pembinaan. Psikoedukasi ini dilakukan dalam bentuk nontraining dengan melakukan seminar oleh pemateri yang diundang dari tim fasilitator dan melakukan sesi diskusi kepada pelatih/pembina Komunitas Esport Indonesia Sulawesi Selatan (ESI Sul-Sel). Penelitian ini menggunakan desing penelitian One-Group Pretest- Posttest Design, dengan subyek 6 orang dengan persentase 3 orang laki-laki (50%) dan 3 orang perempuan (50%).Data dianalisis menggunakan statistik deskriptif, serta berdasarkan hasil analisis statistik inferensial dengan menggunakan rumus uji t. Nilai mean yang didapatkan dari hasil pre-test yaitu 2,66 dan setelah pemberian materi psikoedukasi nilai mean post-test yaitu 5,33. Oleh karena thitung ttabel pada taraf signifikansi 0,05, maka hipotesis nol (H0) ditolak dan hipotesis alternative (Ha) diterima yang berarti bahwa ada pengaruh psikoedukasi ketangguhan mental terhadap motivasi berprestasi atlet selama pembinaan.